Ensaios sobre a luta de classes brasileira: memória, encenação e materiais de arquivos em Era uma vez Brasília (2017) e Democracia em vertigem (2019) - De Souza, Lucas Henrique [UNESP] (My University, 2022)
Era uma vez Brasília (2017), by Adirley Queirós, and Democracia em Vertigem (2019), by Petra Costa, are two contemporary documentary films that deal, each in its own way, with of the main political events in the Brazilian scenario, since the beginning of President Dilma Rousseff's second term, through an essayistic bias. Therefore, this article presents and discusses the essayistic vocation of both documentaries, with regard to the critique of the Brazilian political conjuncture.
Essays on the Brazilian class struggle: Memory, staging and archival materials in Era uma vez Brasília (2017) and Democracia em vertigem (2019)
Keywords: Class struggle; documentary cinema; essay film; politics; rehearsal